Superconducting Quantum Metamaterials from High Pressure Melt Infiltration of Metals into Block Copolymer Double Gyroid Derived Ceramic Templates. (22nd March 2021) - Thedford, R. Paxton; Beaucage, Peter A.; Susca, Ethan M.; Chao, Corson A.; Nowack, Katja C.; Van Dover, Robert B.; Gruner, Sol M.; Wiesner, Ulrich
Abstract: Mesoscale order can lead to emergent properties including phononic bandgaps or topologically protected states. Block copolymers offer a route to mesoscale periodic architectures, but their use as structure directing agents for metallic materials has not been fully realized. A versatile approach to mesostructured metals via bulk block copolymer self‐assembly derived ceramic templates, is demonstrated. Molten indium is infiltrated into mesoporous, double gyroidal silicon nitride templates under high pressure to yield bulk, 3D periodic nanocomposites as free‐standing monoliths which exhibit emergent quantum‐scale phenomena. Vortices are artificially introduced when double gyroidal indium metal behaves as a type II superconductor, with evidence of strong pinning centers arrayed on the order of the double gyroid lattice size. Sample behavior is reproducible over months, showing high stability. High pressure infiltration of bulk block copolymer self‐assembly based ceramic templates is an enabling tool for studying high‐quality metals with previously inaccessible architectures, and paves the way for the emerging field of block‐copolymer derived quantum metamaterials. Abstract : Double‐gyroid structured composites of indium metal and silicon oxynitride ceramic are synthesized via high‐pressure infiltration of a block copolymer self‐assembly derived porous template. Superconducting gyroidal In differs substantially from the bulk metal, with evidence that the structure‐directing polymer dictates material properties. High pressure infiltration improves greatly on previous routes to block copolymer derived mesostructured metals in the bulk regime, and enables the study of block copolymer derived quantum metamaterials.